Earth-Science Education: From all over the World to East-Timor - Marques, Luis (2012)
Earth Science education (ESE) emerges as a relatively new research area and there is an unquestioned need for improving students´ abilities on that field (American Geological Institute, 2008), taking into account that it is important for students’ everyday lives and thus, relevant for scientific literacy. So, the inclusion of a section concerned with this issue, was a very wise decision of the 1st Geological Congress at East-Timor Organising Committee, revealing an up to date vision about education for the XXI century. The paper will be divided in four sections: - Science Education - meaning, epistemology and rationale; - Earth- science-education all over the World in the context of Science Education; - Earth- science education in East-Timor secondary school curriculum; - Earth-science education and challenges for the future